Effective force area and discharge coefficient for reed type valves: A comprehensive data set from a numerical study - Ferreira, Ricardo Lopes; Gasche, José Luiz [UNESP] (Elsevier, 2019)
Radial diffusers have been used as valve model to determine effective force area and discharge coefficient of the flow. A comprehensive data set of these parameters is lacking in the literature. Here, we present numerical results of these parameters for a wide range of incompressible flow operating conditions. The code OpenFOAM® was used to solve the problem for radial diffusers with diameter ratios ranging from 1.15 to 1.7, Reynolds numbers ranging from 3000 to 50,000, and lifts varying from 0.01 to 1.0. The influence of the diameter ratio on the effective force area is found to be high. There is a decrease of up to 80% for small lifts and an increase of 40% for large lifts, but it has a negligible effect on the discharge coefficient. The influence of the Reynolds number on the discharge coefficient is small, up to 8%, but it is large on the effective force area.
Surface de force utile et coefficient de décharge pour les soupapes à lamelles multiples: Un ensemble complet de données tirées d'une étude numérique
Keywords: Compressor; Discharge coefficient; Effective force area; Numerical simulation; Radial diffuser; Reed valve